Intracranial Hemangiopericytoma – A Case Report - Veloso, Gilson Gabriel Viana; Dutra, Raul de Almeida; Dutra, Letícia de Almeida; Meireles, Pedro Teixeira; Abdalla, Douglas Reis; de Almeida Júnior, Luiz Carlos Furtado (Asian Pacific Journal of Cancer Care, 2020)
Hemangiopericytoma is a rare mesenchymal tumor, considered as a subtype of soft tissue sarcomas with an incidence of 3.77/10.000.000 cases. Intracranial hemangiopericytomas account for less than 1% of all primary tumors of the central nervous system. Due to the lack of data available regarding this disease, national and international research provides information derived from retrospective case series and phase I and phase II studies. This is a case report of a young adult diagnosed with intracranial hemangiopericytoma in 2012 with a history of multiple recurrences and therapeutic approaches, assisted in a public health center in southeastern Brazil. Among the treatment options given to the patient, there are surgery, radiotherapy, and systemic chemotherapy (including alkylating and anthracyclines agents). Systemic therapy usually is offered after multiple recurrences or in a metastatic setting; although it increases progression-free survival, there is not enough data on objective response rate and does not yield increased overall survival.